Conventional futures: derivatives in Islamic law of contract. Issue 4 (4th May 2020) - Uddin, Md Akther; Ahmad, Abu Umar Faruq
Abstract : Purpose: This paper aims to compare and contrast the concept of conventional futures contract from the Islamic law of contract perspectives. The underlying theory and practice of Islamic finance is based on the principles of Islamic law of contract. Although the necessity of derivative instruments such as the case with futures contract is essential for developments in Islamic finance, the permissibility of using these instruments still remains a debatable issue. Design/methodology/approach: The paper discusses arguments for and against using derivative instruments as in futures, for example, in light with the Qur'an and Sunnah (the Prophet's traditions), as well as the views of classical scholars, jurists and contemporary researchers. Arguments for and against are analysed systematically to derive a logical conclusion. Findings: The study finds that majority scholars consider futures contracts as non-compliant with the Islamic law due to the fact that selling something that does not exist, deferment in the both counter values, gharar or ambiguity and excessive risk taking, pure speculation and sale of one debt for another. Research limitations/implications: The study focuses narrowly on conventional futures contract. Analysing other financial derivative contracts could be a future research endeavour. Practical implications: The study has so far found the verdict of impermissibility of conventional futures contract in its current form as has been argued by majority scholars in the premise that they do not comply with the Islamic law. Policymakers and industry practitioners need to take this opinion of majority scholars while developing new Islamic financial derivatives. Originality/value: To the best of the author's knowledge, the present research is the first attempt so far that explained the validity of conventional futures by analysing arguments of classical and contemporary jurists, scholars and researchers.